2009
DOI: 10.1074/jbc.m109.056382
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of S-type Phycobiliprotein Lyase

Abstract: We now show that CpcS1 binds PCB and PEB rapidly with bi-exponential kinetics (38/119 and 12/8300 ms, respectively). Chromophore binding to the lyase is reversible and much faster than the spontaneous, but low fidelity chromophore addition to the apo-protein in the absence of the lyase. This indicates kinetic control by the enzyme, which then transfers the chromophore to the apo-protein in a slow (tens of minutes) but stereo-and regioselectively corrects the reaction. This mode of action is reminiscent of chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The resulting K d value of the CpeS⅐3E-PEB complex was 0.7 M, which represents tight binding and which is driven by both favorable enthalpy (⌬H 0 ϭ Ϫ6.1 Ϯ 0.5 kcal/mol) as well as entropy (⌬S 0 ϭ 7.3 Ϯ 1.3 cal/mol/deg) changes upon complex formation. The K d determined for the CpeS⅐3E-PEB complex is in range with values obtained for other lyases (8,39,41,42).…”
mentioning
confidence: 49%
See 4 more Smart Citations
“…The resulting K d value of the CpeS⅐3E-PEB complex was 0.7 M, which represents tight binding and which is driven by both favorable enthalpy (⌬H 0 ϭ Ϫ6.1 Ϯ 0.5 kcal/mol) as well as entropy (⌬S 0 ϭ 7.3 Ϯ 1.3 cal/mol/deg) changes upon complex formation. The K d determined for the CpeS⅐3E-PEB complex is in range with values obtained for other lyases (8,39,41,42).…”
mentioning
confidence: 49%
“…However, DHBV-transferring lyases are at least feasible for cryptophytes with DHBV-containing phycobiliproteins (47). As lyases are also able to detach bilins (8,41,48), CpeS might remove incorrectly bound DHBV from CpeB, but this could not yet be verified in preliminary studies (data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations